Research Status of the Properties and Application in Building Materials of Typical Lithium Slag - Fang Chen; Zhiyou Chen; Xiaoqiong Su; Haiping Zhang (Kuangchan zonghe liyong, 2023)
This is an essay in the field of ceramics and composites. Lithium slag is the solid waste produced in the process of extracting lithium and its compounds from spodumene and lepidolite, in which the content of SiO2 and Al2O3 is as high as 70%. The stacking and landfilling of lithium slag threaten the surrounding environment due to the residual chemicals, and result in the waste of aluminosilicate mineral resources as well. Lithium slag has high specific surface energy and some pozzolanic activity, as enduring high temperature roasting, mechanical grinding and chemical leaching, which make it possible to be used as construction materials. This paper summarizes the latest research results on the application of lithium slag as building materials at home and abroad, focuses on the following aspects: (1) Substituting part of cement as concrete admixture, and the affects on the mechanical properties, carbonization resistance, abrasion resistance, chloride ion penetration and crack resistance of concrete; (2) Substituting clay to produce cement, and its influence on the flexural and compressive strength of cement clinker age; (3) Preparation of architectural ceramics and its impact on mechanical properties and structure; (4) The influence of lithium slag formula on ceramic quality and process performance. Finally, the application research of lithium slag in building materials is summarized and prospected, for the purpose of providing references for the development of lithium slag in building materials with high dosage and good economic benefits.